40 years on: An account of innovation in the regulation of UK telecommunications, in 3½ chapters. Issue 10 (November 2017) - Cave, Martin
Abstract: The past nearly 40 years have seen major developments in telecommunications networks and services, and in how they are regulated. This paper describes innovations in UK telecommunications regulation which have taken place over the period, broken down into stages, beginning with the regulation of the former monopolist by an independent regulator under a price cap, continuing the regulation first of mobile and then, under European Directives, of copper-based broadband, and ending with the diffusion of fibre networks. It is argued that a variety of changes have reduced the scope of innovation over the period, including domestic institutional reform, the limits placed on later decisions by earlier ones (path dependency), and the constraining impact of European Union law and regulation. The paper concludes with some consideration of the effects on future innovation of the UK's withdrawal from the EU. Highlights: Describes innovations in UK network and services regulation since 1980. Identifies some factors promoting or limiting innovation in wholesale and retail services and in spectrum management. Discusses path dependency in regulatory policy over the period. Examines past convergence and possible future divergence between EU and UK regulation.